Rethinking health care systems : private health care provision in India - Berman, Peter A. (1998)
Argues that, given the current situation in many countries a long-term strategy to develop a 'national health service' -type model of health care provision is misguided and wasteful. Highlights the current and potential role of nongovernment health care providers in achieving high levels of access to basic services, using date from an extensive analysis of health care financing and delivery in India.